(untitled) (Research, Society and Development, 2023)
The aim of this study is to highlight the consequences of breast reconstruction with regard to the quality of life of women with mastectomies. This is a narrative review, carried out by searching articles in the Medical Literature Analysis and Retrievel System Online (MEDLINE), Scientific Electronic Library Online (SciELO) and PubMed databases, with the following Health Sciences Descriptors (DeCS ): Breast Neoplasms; Indicators of Quality of Life; Mastectomy; Surgical Oncology; Women’s Health. Selecting articles between the periods 2014 to 2023, in English, Portuguese and Spanish. 4,781 articles were found in MEDLINE, from which 4,772 were excluded. In SciELO, 2,876 articles were found, but 2,866 articles were excluded. In PubMed, 3,483 articles were found, but 3,477 articles were excluded. Totaling 25 articles selected from the three databases. Mastectomy is a surgical therapeutic technique in the treatment of breast cancer, with the total or partial removal of the mammary gland. Being an aggressive procedure, the post-surgery quality of life of women is extremely reduced, from a physical and psychological point of view. Individual daily life also undergoes changes, leaving the patient in more preserved states or away from work activities, corroborating feelings of indisposition and uselessness. Given the various impacts that mastectomy has on the quality of life of women who undergo the procedure, the best option is immediate breast reconstruction and multidisciplinary management in the postoperative period.